2018
DOI: 10.1590/1678-4162-9432
|View full text |Cite
|
Sign up to set email alerts
|

Bioacústica como método de avaliação do comportamento em pastejo de novilhas Girolando

Abstract: RESUMOObjetivou-se validar o método de análise de dados bioacústicos na descrição do comportamento em pastejo de novilhas em área de integração lavoura-pecuária (iLP) e floresta (iLPF). Foram utilizadas oito novilhas Girolando (¾Holandês x ¼Gir) com média de 25±6,8 meses de idade e 268±83kg de peso vivo (PV), distribuídas em delineamento crossover 2x2 (dois sistemas x dois períodos de avaliação). A coleta de dados para análise bioacústica foi realizada utilizando-se gravadores MP3. grazing, rumination, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Period 2 Grazing behavior was recorded from 14 th to 16 th day of the experimental period by bioacoustics (Veit, Salman, Cruz, Souza, & Schmitt, 2018). Audio data were taken by MP3 recorders tied to the heifer's halters for registering the sounds during the activities of grazing, ruminating, resting, and drinking.…”
Section: Crossovermentioning
confidence: 99%
“…Period 2 Grazing behavior was recorded from 14 th to 16 th day of the experimental period by bioacoustics (Veit, Salman, Cruz, Souza, & Schmitt, 2018). Audio data were taken by MP3 recorders tied to the heifer's halters for registering the sounds during the activities of grazing, ruminating, resting, and drinking.…”
Section: Crossovermentioning
confidence: 99%
“…The automated evaluation of images performed by the algorithm showed greater assertiveness ( Table 2 ) in summer (03/05 and 03/06) and in winter (08/01 and 08/03), presenting a lower and similar assertiveness in autumn and spring. This can be explained by the similar levels of solar radiation in the transition seasons (autumn and winter), which exerts a direct influence on the luminosity of the environment due to the angle of solar declination being similar in both seasons, a situation mentioned in another study, which also reported the difficulty in evaluating images at night due to low light [ 32 ].…”
Section: Resultsmentioning
confidence: 95%
“…The chemical composition and digestibility of Xaraés palisade grass, as well as the forage allowance in pastures of both systems are shown in Table 1. The forage bulk density (FBD) and sward height of Xaraés palisade grass are shown in Table 2 Grazing behavior was observed from 14 th to 16 th day of the experimental period using acoustic data (Veit et al, 2018). Audios were captured bymP3 recorders (model PX240, Sony® Corporation, Japan) tied to the heifer's halters for continuously registering the grazing sounds during 48h.…”
Section: Methodsmentioning
confidence: 99%